Coherence analysis of muscle activity during quiet stance - Saffer, Mark; Kiemel, Tim; Jeka, John (Experimental brain research, 2008)
Studies of muscle activation during perturbed standing have demonstrated that the typical patterns of coordination (“ankle strategy” and “hip strategy”) are controlled through multiple muscles activated in a distal-to-proximal or proximal-to-distal temporal pattern. In contrast, quiet stance is thought to be maintained primarily through the ankle musculature. Recently, spectral analysis of inter-segment body motion revealed the coexistence of both ankle and hip patterns of coordination during quiet stance, with the predominating pattern dependent on the frequency of body sway. Here we use frequency domain techniques to determine if these patterns are associated with the same muscular patterns as observed during perturbed stance. Six of the seven muscles measured showed a linear relationship to the sway of at least one body segment, all being leg muscles. Muscle–segment phases were consistent with that required to resist gravity at low frequencies, with increasing phase lag as frequency increased. Visual information had effects only at frequencies below 0.5 Hz, where the shift from in-phase to anti-phase trunk–leg co-phase was observed. These results indicate that co-existence of the ankle and hip pattern during quiet stance involves only leg musculature. Anti-phase movement of the trunk relative to the legs at higher frequencies arises from indirect biomechanical control from posterior leg muscles.